Post-Traumatic Stress and Alcohol-Related Problems Following a College Shooting: Effect of Help-Seeking. (3rd April 2018) - Siebert, Erin C.; Stewart, David G.; Hu, Emily M.; Estoup, Ashley C.; Underbrink, Erin G.; Moore, Lindsay S.
ABSTRACT: Our aim was to test the hypothesized relationships between trauma exposure and alcohol-related problems, mediated by PTS symptoms, moderated by prior trauma exposure and help-seeking. Participants were 244 members of a private university who were enrolled or employed at the school on the date of a campus shooting. Online measures were distributed via e-mail in October 2014, and included the AUDIT, BTQ, PCL-5, and self-report measures of trauma exposure and counseling services utilized. The overall moderated mediation model examining the indirect effect of exposure to trauma on alcohol-related problems through PTSD symptoms, moderated by prior trauma and help seeking was significant, β ( SE ) = .310(.3554), p  = .0001. This study highlights the importance of crisis interventions following trauma exposure.